Analisis Pengukuran Kinerja Realisasi Anggaran Pendapatan Dan Belanja Daerah Dengan Menggunakan Metode Value For Money (Studi Kasus Di Pemerintah Daerah Kota Padang Tahun 2016-2020 - Sitri Wahyuni; Dewi Sartika; Fitrah Mulyani (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
This study uses data collection methods from literature and documentation studies. The purpose of this study is to measure the performance of the realization of the Padang City Government APBD from 2016 to 2020. This study uses the value for money method with the formula for economic ratios, efficiency and effectiveness. The data used is the APBD data and the APBD Realization of the Padang City Government from 2016 to 2020. Based on the results of this study, the 2016 to 2020 economic ratio is considered economical because the percentage is less than 100%, efficiency ratios the 2016 and 2018 are considered inefficient because the percentage is more than 100%, 2019 is considered efficient balanced because the percentage is the same 100% is the same, 2017 and 2020 are considered efficient because the percentage is less than 100%, and the effectiveness of the 2016 to 2020 ratio is considered ineffective because the percentage is less than 100%.